Local Broadcast Journalists and the Trap of Professional Heterogeneity - Casula, Clementina (Professions and Professionalism, 2021)
The ideological tenets of the journalistic professions, historically grounded in the development of modern Western democracies, are increasingly shaken by the changes brought about by a series of technological, economic, and ideological processes challenging the foundations of professionalism. This article considers how these changes influence how work is performed and experienced in Italy by local journalists, providing professional news coverage and programs to communities at the grassroots level through both private and public outlets. The findings of qualitative research adopting a neo-institutional approach are presented and discussed following the analytical frame of the special issue, distinguishing three dimensions (within, between, beyond) related to the increased differentiation and the changing role of professionals in post-industrial societies. Conclusions point to the fact that the resulting heterogeneity if accepted without granting the necessary conditions to maintain professional standards, may bring into question the feasibility of a professional community.